IMPLEMENTATION OF SERVICE QUALITY WITH PEDIATRIC PATIENT SATISFACTION IN THE INPATIENT WARD OF BUNG HATTA HOSPITAL CLASS III REKSODIWIRYO PADANG - Transyah, Chichi Hafifa; Oresti, Syalvia (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Healthcare service quality is an important factor influencing patient satisfaction, particularly in pediatric nursing services in hospitals. The SERVQUAL model, which includes the dimensions of tangible, reliability, responsiveness, assurance, and empathy, is widely used to evaluate healthcare service quality. This study aimed to analyze the relationship between service quality and pediatric patient satisfaction in the Bung Hatta Inpatient Ward of Tk III Dr. Reksodiwiryo Hospital, Padang. This study employed a quantitative approach with an analytic descriptive design and a cross-sectional method. The sample consisted of 30 respondents who were parents or guardians of pediatric patients hospitalized for at least three days. Respondents were selected using an accidental sampling technique. Data were collected using a SERVQUAL-based questionnaire with a Likert scale and analyzed using univariate and bivariate analysis with the Chi-square test at a significance level of 0.05. The results showed that the majority of respondents were satisfied with nursing services (80%). Bivariate analysis indicated significant relationships between the tangible (p=0.033), reliability (p=0.049), and assurance (p=0.040) dimensions and pediatric patient satisfaction. However, responsiveness and empathy dimensions were not statistically associated with patient satisfaction (p>0.05). In conclusion, nursing service quality is associated with pediatric patient satisfaction in several SERVQUAL dimensions, particularly tangible, reliability, and assurance. Continuous improvement in nursing service quality is necessary to enhance satisfaction among pediatric patients and their families in hospital settings.